I Do, Thou Shalt Not: Religious Opposition to Same‐Sex Marriage in Britain. Issue 2 (2nd May 2013) - Kettell, Steven
<x xml:space="preserve">Abstract</x> Proposals to legalise same‐sex marriage have provoked one of the most high‐profile and controversial political debates in recent years. The plans, being introduced by the governments at Westminster and Holyrood, have divided political and public opinion and have attracted widespread opposition from religious groups. However, while religious attitudes to homosexuality are shaped by theological concerns, religious justifications have been largely absent from the case against same‐sex marriage. Instead, religious groups have presented their arguments in secular terms centred on tradition, social utility, democratic values and the threat to religious rights and freedoms. This particular framing of the issue reflects processes of secularisation, a growing use of identity politics and the composition of religious groups themselves.